2018
DOI: 10.32718/nvlvet9202
|View full text |Cite
|
Sign up to set email alerts
|

Тhe content of calcium and phosphorus in the blood of cows with a different tonus of the autonomic nervous system

Abstract: Zhurenko, O.V., Karpovskiy, V.I., Danchuk, О.V., & Kravchenko-Dovga, Yu.V. (2018). Тhe content of calcium and phosphorus in the blood of cows with a different tonus of the autonomic nervous system. Scientific MessengerResearch was conducted on cows of the Ukrainian black-and-white breed of the 2-3 lactation. Tonus of the autonomic nervous system (ANS) of cows was determined using trigeminovagal reflex (TVR). According to the obtained results, an animal was designate as normotonics, sympatheticotoniсs or vagoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
5
Order By: Relevance
“…The autonomic nervous system maintains homeostasis and regulates the stability of the internal matrix fluid needed to sustain life. It is found that the indicators of metabolism in the body of farm animals depend on the tone of the autonomic nervous system (Zhurenko et al, 2018). The high level of productivity of poultry depends on the intensity of metabolic processes, which promotes rapid absorption of nutrients, early maturity and high productivity (Kyryliv et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic nervous system maintains homeostasis and regulates the stability of the internal matrix fluid needed to sustain life. It is found that the indicators of metabolism in the body of farm animals depend on the tone of the autonomic nervous system (Zhurenko et al, 2018). The high level of productivity of poultry depends on the intensity of metabolic processes, which promotes rapid absorption of nutrients, early maturity and high productivity (Kyryliv et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Серцево-судинна система, до складу якої входить серце та кровоносні судини, є однією із інтегруючих систем організму, що відіграє важливу роль у підтриманні його гомеостазу і сприяє реалізації функцій нервової, ендокринної системи та органів імунного захисту (Zhurenko et al, 2018). Вона регулює кровопостачання органів, тиск крові, забезпечує відтік лімфи органів і транспорт її у вени (Khomych et al, 2020).…”
Section: вступunclassified
“…Автономна нервова система підтримує гомеостаз та регулює стабільність внутрішньої матричної рідини, необхідної для підтримання життя (Cannon, 1939). Встановлено, що показники обміну речовин в організмі сільськогосподарських тварин залежать від тонусу автономної нервової системи (Zhurenko et al, 2018). Високий рівень продуктивності сільськогосподарської птиці залежить від інтенсивність обмінних процесів, що сприяє швидкому засвоюванню поживних речовин, ранній скоростиглості та високій продуктивності (Kyryliv et al, 2015).…”
Section: вступunclassified